Gender Bias in AI's Perception of Cardiovascular Risk - Margaux Achtari; Adil Salihu; Olivier Muller; Emmanuel Abbé; Carole Clair; Joëlle Schwarz; Stephane Fournier (JMIR Publications, 2024)
The study investigated gender bias in GPT-4's assessment of coronary artery disease risk by presenting identical clinical vignettes of men and women with and without psychiatric comorbidities. Results suggest that psychiatric conditions may influence GPT-4's coronary artery disease risk assessment among men and women.